Attention Capture By Episodic Long-term Memories: Evidence from Eye Movement Data - (:unkn) unknown (My University, 2020)
Successfully navigating the world on a moment-to-moment basis requires the interaction of multiple cognitive processes. Therefore, studies that examine when and how these fundamental processes interact can provide important insights into how we behave. Many studies indicate that long-term memory can facilitate search for a target object (e.g., contextual cueing), however, the ways in which long-term memory might capture attention and disrupt goal-directed behavior have not been well studied. In five experiments, questions about whether encoded objects might capture attention, even when they are task-irrelevant, were addressed. Each experiment began with an encoding phase, where participants were instructed to commit scene-objects pairs to memory. Then, participants completed a visual search task where they were instructed to make a single eye movement to either the unique shape (Experiments 1, 4, and 5; e.g., a square among circles) or the unique color (Experiments 2 and 3; e.g., the blue shape among other gray shapes) in search displays as quickly and accurately as possible. Occasionally, one of the objects in the search displays was one of the encoded objects, and sometimes one of the encoded scenes was presented prior to the search display. We found, across experiments, that attention was captured by task-irrelevant encoded objects, and that the greatest amount of capture was documented following scene cues. Further, more time was spent fixating encoded objects when they captured attention and scene cues were presented before search displays. Lastly, we found that when saccades were initiated to targets as instructed, saccade latencies were slower when scene cues preceded search displays. Initially, we had interpreted this as an effect of covert capture by the encoded objects, however, the final two experiments suggest that the slowdown is more likely to be the result of presenting complex visual information prior to search displays. Together, the results of these experiments suggest that episodic long-term memories can capture attention and does so in a way that is consistent with the idea that selection history can guide where attention is directed.
Keywords: Attention; Attention Capture; Eye Tracking; Memory